Work Groups’ Cohesion in the County of Satu Mare: An Empirical Comparative Analysis of Employers’ and Employees’ Perception - Lazăr, Vasile; Teodoru, Mircea Constantin; Ardelean, Doru Ioan (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The paper compares the views of employers and employees regarding the use of work cohesion instruments within companies from Satu Mare County. The comparison is based on data collected and processed within the project HURO/0901/264/2.2.2 implemented in partnership by "Vasile Goldiș" Western University and University of Debrecen and financed by European Union through ERDF under Hungary-Romania 2007-2013 Programme, in 2012, and on data collected and processed in 2013-2014, in a new field research applied to employees of 75 companies from Satu Mare County.